The - Moody, T. W. (Clarendon Press, 2007)
This edition of the writings of Theobald Wolfe Tone (1763-98), barrister, United Irishman, agent of the Catholic Committee and later an officer in the French revolutionary army, is intended to comprehend all his writings and largely to supersede the two-volume Life of Theobald Wolfe Tone. ..written by himself that was edited by his son William, and published at Washington in 1826. It consists mainly of Tone's correspondence, diaries, autobiography, pamphlets, public addresses, and miscellaneous memoranda (both personal and public); it is based on the original MSS if extant or the most reliable printed sources